PENGARUH KARAKTERISTIK KOMITE AUDIT TERHADAP RISIKO KEBANGKRUTAN DENGAN KECURANGAN LAPORAN KEUANGAN SEBAGAI VARIABEL MEDIASI - Amaliyah, Dina; Putri, Dhika Maha (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.03.TAHUN.2024, 2024)
This study investigates the impact of audit committee competency and meeting frequency on bankruptcy risk, considering financial statement fraud as a potential mediating factor. This research focuses on construction sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period, by selecting 16 companies through purposive sampling. The methodology used included logistic regression and path analysis for data examination. The findings show that audit committee competency and meeting frequency have no influence on fraud. Audit committee competency was also found to have no influence on bankruptcy risk. On the other hand, meeting frequency shows a significant ability to reduce the risk of bankruptcy in financial statements. The mediating role of fraud in the relationship between audit committee attributes (competence and frequency) and bankruptcy risk is not supported. Apart from that, the last hypothesis shows that fraud has no effect on bankruptcy risk.